OBSERVATION OF AI TEXT TO IMAGE USAGE ON THE CREDIBILITY OF VISUAL ARTWORKS - Aliya, Tasya Putri; Aurelia, A. Talitha Rezky; Najmi, Nisa Salvia; Apsarini, Fira Areta; Rakhmawati, Nur Aini (Journal of Information System, Informatics and Computing, 2023)
Artificial Intelligence (AI) has advanced the technology of AI Text-to-Image, such as the Midjourney platform, which is an application that creates images based on text prompts. However, this raises the question of whether AI works from Midjourney do not violate copyright. This study uses Roland Barthes' semiotics theory and The Liang Gie's aesthetic theory to analyze the artwork produced by Midjourney. The results of the study show that Midjourney is able to create new images by combining elements from various photos to create new images that have unity, harmony, and balance based on the given text prompts. In other words, AI works do not directly copy or imitate existing artwork on the internet. This study provides a deeper understanding of the working principles of AI Text-to-Image platforms and confirms that the results produced by AI such as Midjourney have unique artistic value and do not violate copyright. Although there is debate surrounding the use of AI in art, the results of this study support the view that AI can be a creative and innovative tool in creating unique and new visual artworks.